The Role of GDF15 in Regulating the Canonical Pathways of the Tumor Microenvironment in Wild-Type p53 Ovarian Tumor and Its Response to Chemotherapy - Izaguirre, Daisy I. (Cancers (Basel), 2020)
SIMPLE SUMMARY: Patients with wild-type p53 ovarian cancer appear to have a poorer survival rate than those with mutant p53 due to resistance to chemotherapy. The mechanism underlying this observation is not clearly understood. The aim of this study was to identify potential biomarkers regulated by p53 that conferred resistance using in vitro and in vivo studies. Growth differentiation factor 15 (GDF15) expression was demonstrated to be controlled by p53 in both ovarian cancer cell lines and orthotopic mouse models. The histological and RNAseq studies of the GDF15-knocked down, A2780 cell line-induced tumor revealed that the ratio and canonical pathways of stromal/tumor were modified by secretory GDF15. ABSTRACT: Background: The standard treatment of ovarian cancer is surgery followed by a chemotherapeutic combination consisting of a platinum agent, such as cisplatin and a taxane-like paclitaxel. We previously observed that patients with ovarian cancer wild-type for p53 had a poorer survival rate than did those with p53 mutations. Thus, a better understanding of the molecular changes of epithelial ovarian cancer cells with wild-type p53 in response to treatment with cisplatin could reveal novel mechanisms of chemoresistance. Methods: Gene expression profiling was performed on an ovarian cancer cell line A2780 with wild-type p53 treated with cisplatin. A gene encoding a secretory protein growth differentiation factor 15 (GDF15) was identified to be highly induced by cisplatin treatment in vitro. This was further validated in a panel of wild-type and mutant p53 ovarian cancer cell lines, as well as in mouse orthotopic models. The mouse tumor tissues were further analyzed by histology and RNA-seq. Results: GDF15 was identified as one of the highly induced genes by cisplatin or carboplatin in ovarian cancer cell lines with wild-type p53. The wild-type p53-induced expression of GDF15 and GDF15-confered chemotherapy resistance was further demonstrated in vitro and in vivo. This study also discovered that GDF15-knockdown (GDF15-KD) tumors had less stromal component and had different repertoires of activated and inhibited canonical pathways in the stromal cell and cancer cell components from that of the control tumors after cisplatin treatment. Conclusions: GDF15 expression from the wild-type p53 cancer cells can modulate the canonical pathways in the tumor microenvironment in response to cisplatin, which is a possible mechanism of chemoresistance.